Origins, actions and dynamic expression patterns of the neuropeptide VGF in rat peripheral and central sensory neurones following peripheral nerve injury - Costigan Michael; Hathway Gareth J; Baccei Mark; Low Lucie; Theodorou Andria; Koch Stephanie; Ingram Rachel; Moss Andrew; Salton Stephen R; Fitzgerald Maria (Molecular Pain, 2008)
Abstract Background The role of the neurotrophin regulated polypeptide, VGF, has been investigated in a rat spared injury model of neuropathic pain. This peptide has been shown to be associated with synaptic strengthening and learning in the hippocampus and while it is known that VGFmRNA is upregulated in dorsal root ganglia following peripheral nerve injury, the role of this VGF peptide in neuropathic pain has yet to be investigated. Results Prolonged upregulation of VGF mRNA and protein was observed in injured dorsal root ganglion neurons, central terminals and their target dorsal horn neurons. Intrathecal application of TLQP-62, the C-terminal active portion of VGF (5–50 nmol) to naïve rats caused a long-lasting mechanical and cold behavioral allodynia. Direct actions of 50 nM TLQP-62 upon dorsal horn neuron excitability was demonstrated in whole cell patch recordings in spinal cord slices and in receptive field analysis in intact, anesthetized rats where significant actions of VGF were upon spontaneous activity and cold evoked responses. Conclusion VGF expression is therefore highly modulated in nociceptive pathways following peripheral nerve injury and can cause dorsal horn cell excitation and behavioral hypersensitivity in naïve animals. Together the results point to a novel and powerful role for VGF in neuropathic pain.